Timing of procedural stroke and death in asymptomatic patients undergoing carotid endarterectomy: individual patient analysis from four RCTs. Issue 6 (12th March 2020) - Poorthuis, M. H. F.; Bulbulia, R.; Morris, D. R.; Pan, H.; Rothwell, P. M.; Algra, A.; Becquemin, J.‐P.; Bonati, L. H.; Brott, T. G.; Brown, M. M.; Calvet, D.; Eckstein, H.‐H.; et al.
Abstract : Background: The effectiveness of carotid endarterectomy (CEA) for stroke prevention depends on low procedural risks. The aim of this study was to assess the frequency and timing of procedural complications after CEA, which may clarify underlying mechanisms and help inform safe discharge policies. Methods: Individual‐patient data were obtained from four large carotid intervention trials (VACS, ACAS, ACST‐1 and GALA; 1983–2007). Patients undergoing CEA for asymptomatic carotid artery stenosis directly after randomization were used for the present analysis. Timing of procedural death and stroke was divided into intraoperative day 0, postoperative day 0, days 1–3 and days 4–30. Results: Some 3694 patients were included in the analysis. A total of 103 patients (2·8 per cent) had serious procedural complications (18 fatal strokes, 68 non‐fatal strokes, 11 fatal myocardial infarctions and 6 deaths from other causes) [Correction added on 20 April, after first online publication: the percentage value has been corrected to 2·8]. Of the 86 strokes, 67 (78 per cent) were ipsilateral, 17 (20 per cent) were contralateral and two (2 per cent) were vertebrobasilar. Forty‐five strokes (52 per cent) were ischaemic, nine (10 per cent) haemorrhagic, and stroke subtype was not determined in 32 patients (37 per cent). Half of the strokes happened on the day of CEA. Of all serious complications recorded, 44 (42·7 per cent) occurred on day 0 (20 intraoperative, 17 postoperative, 7 with unclear timing), 23 (22·3 per cent) on days 1–3 and 36 (35·0 per cent) on days 4–30. Conclusion: At least half of the procedural strokes in this study were ischaemic and ipsilateral to the treated artery. Half of all procedural complications occurred on the day of surgery, but one‐third after day 3 when many patients had been discharged. Abstract : At least half of the procedural strokes in this study were ischaemic and ipsilateral to the treated artery. Half of all procedural complications occurred on the day of surgery, but one‐third after day 3 when many patients had been discharged. Reported in‐hospital stroke or death rates might underestimate true risks after carotid endarterectomy. Half the strokes occurred after the day of surgery Abstract : Antecedentes: La efectividad de la endarterectomía carotídea ( carotid endarterectomy, CEA) en la prevención de un accidente cerebrovascular depende de que este procedimiento tenga pocos riesgos. El objetivo de este estudio fue evaluar la frecuencia y el momento de aparición de las complicaciones tras una CEA, lo que podría clarificar los mecanismos subyacentes y ayudar a establecer una política de altas hospitalarias segura. Métodos: Se utilizaron los datos de los pacientes incluidos en cuatro grandes ensayos de intervención carotídea (VACS, ACAS, ACST‐1 y GALA; 1983‐2007). Para el presente análisis se utilizaron los datos de pacientes sometidos a CEA por estenosis de la arteria carótida asintomática recogidos inmediatamente tras la aleatorización. Se consideraron diferentes intervalos entre el procedimiento, la muerte o el accidente cerebrovascular: intraoperatorio día 0, postoperatorio día 0, postoperatorio días 1‐3 y postoperatorio días 4‐30. Resultados: En el análisis se incluyeron 3.694 pacientes. Se detectaron complicaciones graves relacionadas con el procedimiento en 103 (2, 8%) pacientes (18 accidentes cerebrovasculares fatales, 68 accidentes cerebrovasculares no fatales, 11 infartos de miocardio fatales y 6 muertes por otras causas). De los 86 accidentes cerebrovasculares, 67 (78%) fueron ipsilaterales, 17 (20%) contralaterales y dos (2%) vertebrobasilares. Los accidentes cerebrovasculares fueron isquémicos en 45 (52%) casos, hemorrágicos en 9 (10%) y no se pudo determinar el subtipo de ictus en 32 (37%). La mitad de los accidentes cerebrovasculares ocurrieron el día de la CEA. De todas las complicaciones graves registradas, 44 (43%) ocurrieron en el día 0 (20 intraoperatorias, 17 postoperatorias y 7 en períodos poco definidos), 23 (22%) entre los días 1‐3 y 36 (35%) entre los días 4‐30. Conclusión: En este estudio, al menos la mitad de los accidentes cerebrovasculares relacionados con la CEA fueron isquémicos e ipsilaterales respecto a la arteria tratada. La mitad de todas las complicaciones de la CEA ocurrieron el día de la cirugía, pero un tercio de los casos se presentaron después del día 3, cuando muchos pacientes ya habían sido dados de alta.